الغاء الدفتر العقاري - جراردة شيماء -حاجي أمينة (جامعة المسيلة, 2020)
إن إعداد الدفتر العقاري لا يتحقق إلا عن طريق القيام بعملية مهمة وهي عملية المسح العام للأراضي، والتي تسير وفق إجراءات تقنية وقانونية، بعد الانتهاء من هذه العملية وحتى تكتسي وثائق المسح العام القوة الثبوتية، يجب إيداعها لدى المحافظة العقارية وفق القوانين المنظمة لها من أجل ضمان تطبيق قواعد الإشهار بصورة دقيقة، وبعد إمضاء المحافظ العقاري على محضر تسليم هذه الوثائق يشرع في عملية إعداد البطاقات العقارية وتأسيس السجل العقاري، وترقيم العقارات ترقيم مؤقت أو نهائي حسب الآجال والوضعية القانونية للعقار، بمجرد وصول العقار لمرحلة الترقيم النهائي دون اعتراض، يصبح من حق المالك الحصول على الدفتر العقاري. كما يرد على الدفتر العقاري مجموعة من الإشكالات القانونية مما يعرضه للطعن قضائيا أمام الجهة المختصة ، من أجل حماية الحقوق العينية العقارية فترفع الدعوى أمام القضاء العادي، أما فيما يخص إلغاء الدفتر العقاري أمام القضاء العادي فإنها غالبا ما ترفض هذه الدعوى لعدم التأسيس أو عدم الاختصاص وبالتالي يرجع الاختصاص إلى القضاء الإداري. Abstract : The preparation of the real estate book is only achieved through an important process , which is the general survey of lands, which is carried out according to technical and legal procedures, after the completion of this process and until the general survey documents have evidentiary strength, they must be deposited with the real estate governorate in accordance with the laws regulating them in order to ensure that the advertising rules are strictly applied, and after the real estate portfolios sign the minutes of delivery of these documents, the process of preparing real estate cards and establishing the real estate registry and numbering the real estate will begin. Temporary or final numbering according to the terms and legal status of the property.Once the property reaches the final numbering stage without recognition, it becomes the right The owner has access to the real estate book. Also, a set of legal problems are presented to the real estate book, which exposes it to appeal cases before the competent authority, in order to protect real estate rights, and the lawsuit is filed before the ordinary courts, as for the cancellation of the real estate book before the ordinary court, this case is often rejected due to lack of establishment or knowledge of specialization. We return the jurisdiction to the administrative judiciary.
Keywords: الدفتر العقاري ى-ألغاء